A hidra cearense: rotas de retirantes e escravizados entre o Ceará e as fronteiras do Norte (1877-1884) - Barboza, Edson Holanda Lima (2013)
We will analyze interferences exerted by refugees from Ceará in the composition of migratory routes towards the provinces of the far North - Piauí, Maranhão, Pará and Amazonas. It interprets the impact of Diaspora of Ceará, between the years 1877 and 1880, due to drought, and how it was perceived by enslaved workers from Ceará and neighboring provinces as opportunities to reverse their identities and lifestyles, enabling captives or criminals to access denied projects of mobilization and social inclusion. The conflicting trajectories involved unruly captives and free paupers traversing provincial centers, public works and agricultural colonies. In this way, enslaved, national and foreign settlers formed contact zones in which it was possible to exchange experiences and solidarities. One main zone was the Núcleo Colonial de Nossa Senhora do Carmo de Benevides, next to Belém, a space planned by local elites to boost agricultural production in Pará, which, however, was a place of unexpected alliances joints that turned this core in place of riots and in focus of abolitionist struggles